MAIN ASPECTS OF WASTE RECYCLING FOR METALLURGICAL FACILITYS ON THE EXAMPLE OF INDUSTRY OF SOUTHERN UKRAINE - Sereda, Borys; Mukovs’ka, Darya (Scientific Journal "Metallurgy", 2021)
To date, the activities of metallurgical enterprises are accompanied by a large amount of ironcontainingwaste, much of which is still not used, stored in dumps, storages, settling tanks.Therefore, in recent years there is a growing need for their comprehensive disposal. Suchwastes include metallurgical slags. Slag is formed in the process of steel smelting. Slag accountsfor a significant part of metallurgical waste. Slag dumps are man-made deposits of amixture of metal and oxide components, each of which is a valuable raw material. Slag dumpsand dumps occupy large areas and have a negative impact on the environment. The main wayto reduce the damage from metallurgical slag to the environment is to recycle it. Processing andutilization of slag allows to solve one of the most important ecological tasks - cleaning of territoriesfrom large-tonnage wastes, which are slags of metallurgical production. The plants are interestedin organizing the process of slag processing not only for environmental but also foreconomic reasons. According to research, the metal content in the slag reaches 15%. Given theshortage of iron ore for many metallurgical enterprises, namely, the south of Ukraine, the use ofwaste of own production in the technological cycle is largely the main and appropriate reserveto reduce production costs and increase economic performance of metallurgical production.This article analyzes the main aspects of recycling of metallurgical enterprises, considers theoperation of the slag processing plant of the metallurgical enterprise of southern Ukraine. Theproduction functions, structure, capacity of the shop are described. The volume, structure, mainproduction indicators of the slag processing plant for 12 consecutive months are analyzed. Themain types and volumes of processed technological waste are given. The expediency of theiruse in own production is shown.